A Quasi-Consulting Project Involving Accounting and Management Students. - Harris, John K.; Hodgetts, Richard M. (The Accounting Review, 1972)
ABSTRACT Couched in terms of the contrast between certain aspects of the undergraduate curriculum and the professional role of students after graduation, this paper reports the design and results of an interdisciplinary, quasi-consulting project, which involved accounting and management students. The research findings include a quantitative measure of the impact of accounting consultants on the project and a qualitative gauge of the overall learning experience that developed. Based on the findings, the research project appears to have been valuable from both a pedagogical and an applied viewpoint. Further research in this area could promote development of more effective accounting and management curricula. Students majoring in accounting frequently complete their degree requirements without taking a course in business decision making that allows them to assume a consulting or advisory role. Even when accounting students elect a course in business policy, they perform as managers rather than as consultants. After graduation, however, accountants often find themselves serving in a consulting capacity. This ,difference between academic requirements for an accounting degree and the manner in which professional accountants function suggests that accounting education could be enhanced by conducting appropriate projects, which would permit accounting students to act as quasiconsultants.(n1) A similar contrast also confronts students majoring in management. As undergraduates, management majors are provided training in the theories and techniques of decision making. In the business world, however, managers draw upon technical expertise of their staff advisors. Management students, therefore, may benefit from working with quasi-consultants. The purpose of this paper is to report the design and results of an interdisciplinary, quasi-consulting project, which involved accounting and management students. The research findings include a quantitative measure of the impact of